Music for the Last Supper: The Dramatic Significance of Mozart’s Musical Quotations in the Tafelmusik of Don Giovanni - Chong, Nicholas Junkai (Current Musicology, 2011)
In the Act II finale of Mozart’s Don Giovanni, as the title character enjoys his dinner, a domestic wind band, called a Harmonie in Mozart’s time, plays some Tafelmusik – music intended to accompany a meal. The Tafelmusik that Mozart chose for Don Giovanni’s last supper consists of melodies quoted from three contemporaneous opere buJfe (Example 1): Vincente Martin y Soler’s Una cos a rara (1786), Giuseppe Sarti’s Fra i due litiganti il terzo gode (1782), and Mozart’s own The Marriage of Figaro (1786). Such musical quotation is a specific type of allusion. As Christopher Reynolds has pointed out, an allusion is not simply a “reference to another work made by means of a resemblance;’ but must be intentional; since “motivic possibilities are finite;’ unintended similarities between two works are bound to occur. Quotation employs an especially high degree of resemblance to the source being alluded to; in the case of the Tafelmusik, whole melodies are reproduced from other operas, not just smaller motives. “Quotations,” Reynolds writes, “are neither more nor less meaningful than less exact references-only a different degree of artistic appropriation.” I would go further and argue that quotations, in comparison to less exact forms of allusion, demonstrate intentionality. Leaving aside situations where there exists documentary proof of a composer’s intentions, it is always possible to argue that resemblances between two pieces are unintended. With quotations, however, this possibility is greatly diminished because the reference is much more exact. In the Tafelmusik, not only are the melodies unmistakable quotations from other operas; Mozart even has Leporello announce them as such to the audience. There can thus be no doubt that Mozart intended these quotations to be heard and easily identified. As the quotations from Martin’s and Sarti’s operas begin, Leporello announces their titles. “Bravi! ‘Cosa raraT’ he cries (mm. 53-54), then later “Evvivano i ‘LitigantiT’ (mm. 123-25). Finally, Leporello hears the quotation from Figaro-the tune of Figaro’s aria “Non pili andrai:’ This time, instead of announcing the title of Mozart’s earlier opera, he sings, “Questa poi la conosco pur troppo” (mm. 164-66) “This one, then, I know only too well”). At the Prague premiere of Don Giovanni, this line would have had a special significance for the local audience, for Felice Ponziani, the baritone singing Leporello, had also sung the role of Figaro-and “Non pili andrai” – in Prague the year before.